KAYU TERPETRI DI SARAWAK: SATU PANDANGAN (PETRIFIED WOOD OF SARAWAK: AN OVERVIEW) - Abd Kadir, Askury (Institut Alam Sekitar dan Pembangunan (LESTARI) UKM, 2009)

(untitled)
ABSTRACT: The Sarawak petrified woods occurred within the Tertiary Kayan Sandstone in the vicinity of Bungo Range which are threatening and going to be permanently destroyed by illegal exploitation activities. The uncontrolled illegal exploitation caused the geological artifacts being widely trading for antique collector, exotic items or ecstatic value without paying any fees or royalty to the government. The petrified wood, including palm and conifer trees had undergone petrification within million of years, where their original wood features replaced by silica minerals, such as opal and chalcedony. The transformation processes are unique in term of petrification, and can be translated into very high ecstatic and scientific values for geoscience communities, and cultural value for local folklore. Hence, the wood structures including their cells are retained and can be observed neither macroscopically nor microscopically. The varieties of colour and degree of preservation of the Sarawak petrified woods are attractive and have an ability to compete with other petrified wood reported around the world. The relevant government agencies are greatly required for promotion and publicise our hidden treasures for our future generation. The SWOT analysis for petrified wood revealed a lot of opportunities for geoscience community to safeguard these treasures from any humanities destruction. Nevertheless, it can be transformed into onsite research centre that attract local and international researchers. The strength obtained from this analysis encompasses on the existing infrastructure around the area might be a momentum for the development, viz: Borneo Height (highlands & golf tourism), Kg. Annah Rais (cultural village for Bidayuh ethnic group), Semenggok (Orang Utan Rehabilitation Centre), hot spring (under construction) and Kg Sadir (Bidayuh village).